Methods of Terrorism Financing: Criminal Procedural Obstacles to the Prevention of Crime in Germany, Liechtenstein, Austria and Switzerland - Teichmann, Fabian (Internationales und Europaeisches Strafverfahrensrecht Ser., 2021)
This monograph deals with this research gap and shows which criminal procedural barriers and hurdles significantly impede the fight against terrorist financing, but also other criminal offences.